Right to Education in India: A Journey through Lenses of Judiciary - Molia, Dr. Tarkesh J.; Upadhyay, Dr. Vikash Kumar; Sharma, Mr. Arpit (The journal of contemporary issues in business and government, 2021)
Education is very essential for the human development. The elementary education should be available to every citizens so they may be enlightened. The aim of the paper is to explore journey of elementary education in India through the lenses of law and judiciary. This paper has been divided in seven parts. The first part introduce the need of elementary education. Second part deals with the Constituent Assembly Debate on need of elementary education in constitution of India. Third part of this paper explore the pre-86th Constitutional Amendment Act, 2002. The fourth part deals situation with post 86th Constitutional Amendment Act, 2002. The fifth part explore the salient features of the ‘The Right to Free and Compulsory Education Act, 2009’. The sixth part deals the situation after the enactment of ‘Right to Free and Compulsory Education Act, 2009’. Last and seventh part has conclusion.